Simulation study on a novel snapback-free and low turn-off loss reverse-conducting SOI-LIGBT with P-type double trench gates on the anode region. (5th September 2019) - Zhang, Bingke; Kong, Moufu; Yi, Bo; Hu, Huan; Chen, Weizhen; Chen, Xingbi
Abstract: A snapback-free and low turn-off loss silicon on insulator LIGBT with reverse-conducting capability (RC-LIGBT) is proposed and investigated in this paper. By employing P-type polysilicon (P-poly) double trench gates at the anode region of the proposed device (DTA-LIGBT), the n-drift region located between the P-type double trench gates (DPL region) is fully depleted because of the work function difference between the P-poly and the DPL region. Thus the resistance between the shorted N+ anode and the N-buffer is significantly increased, which effectively eliminates the snapback phenomenon. The simulation results reveal that the proposed structure completely eliminates the snapback effect with the reverse conducting voltage of 1.05 and 1.25 V at J = 100 and 400 A cm −2, respectively. In addition, the LDMOS is automatically turned on when the device is operating at high voltage, which improves the immunity of latch-up and the short-circuit capability of the device. Simultaneously, the turn-off time of the proposed structure and the turn-off loss are reduced creased by 53.5% and 53% compared with that of the separated shorted-anode LIGBT (SSA-LIGBT), respectively. Moreover, the short-circuit time of the DTA-LIGBT (p) is increased by 186% compared with the SSA-LIGBT.